Health Financing Options for Samoa : Challenges and Opportunities - Anderson, Ian (World Bank, Washington, DC, 2014)
Samoa currently faces two important public policy challenges in the health sector. One is to stem, and then reverse, the rapid rise of non-communicable diseases (NCDs). The second challenge is to put the country on a health-financing path that is effective, efficient, and financially affordable and sustainable. The two challenges are interconnected. This discussion paper examines eight options to address these challenges. The eight options are the following: (1) increasing government expenditure via higher general taxation; (2) increasing government expenditure via deficit financing; (3) increasing the share of government expenditure to health; (4) increasing external and donor financing; (5) increasing specific taxes; (6) mobilizing additional nongovernment resources via insurance (including social health insurance, and community and private insurance); (7) increasing cost-recovery measures; and (8) increasing efficiency. The paper concludes that the chief opportunity arises from more efficient use of resources already in the health system that are not presently used to maximum effect. Improving technical and allocative efficiency of the existing system has the potential to make a large difference and is technically feasible.